Online da'wah as hijra commodification practice in media by @Indonesiatanpapacaran movement - Aini, Syarifah Nur; Akalili, Awanis (Informasi, 2021)
Dakwah discussing Islamic values are not only obtainable through religious lectures, television broadcasts, or certain book category. Dakwah could also be performed by using social media; a medium that is dominated by milennials. Dakwah performed by @indonesiatanpapacaran, is an example for dakwah movement in social media. This account is favored by individuals who pursue "hijrah" (hegira/hijra). Not only introducing the nurture of Islamic values, this account also has its profitable business going. Some religious narrations could function as commodity materials, both online and offline. In the end of the day, the capitalist could gain great benefit by this account's movement. The objective of this study is to obtain an overview of commodification process performed by @indonesiatanpapacaran. Research method used is content analysis. Data collection was conducted by analyzing all contents posted in @indonesiatanpapacaran Instagram account. Some data including contents, values, and even narrations, are the highlight of the analysis. All contents in marriage principals could be seen as potential contents made use by Indonesia Tanpa Pacaran movement.